Long-run relationships and dynamic interactions between housing and stock prices in Malaysia - Ibrahim, Mansor; Padli, Jaharudin; Abdul Hamid, Baharom (Asian Academy of Management (AAM) and Penerbit Universiti Sains Malaysia, 2009)
Economists recognise that macroeconomic and financial variables have an impact on housing prices. In this study, we focus on the relationship between housing prices and stock prices in Thailand using quarterly data from the first quarter (Q1) of 1995 till the last quarter (Q4) of 2006. The analysis is conducted within a multivariate setting that incorporates the Stock Exchange of Thailand Composite Index and housing prices, the real gross domestic product and the consumer price index. In this paper, the autoregressive distributive lags (ARDL) cointegration test is applied to examine the variables' long-run relationships. We then employ the ARDL, DOLS and ML approaches to estimate the long-run parameters and impulse response functions based on a vector autoregression (VAR) framework to explore their dynamic interactions. Our results indicate positive relationships between housing prices and the macroeconomic and financial variables chosen. As regards their dynamic interactions, we note significant responses of housing prices to shocks in the three variables.